Evaluasi Status Kesuburan Tanah pada Pertanian Lahan Kering Berbasis Sistem Informasi Geografis di Kecamatan Baturiti - Jencristy Gilberd Sitanggang; Ni Made Trigunasih; A.A. Nyoman Supadma (Fakultas Pertanian, Universitas Udayana, 2022)
Baturiti District is located in the highlands and is one of the largest producers of horticultural agricultural products in Bali Province. productivity of seasonal horticultural crops, namely tomato plants (31,617 tons/ha); chili plants (8,122 tons/ha); Chinese cabbage (61,889 tons/ha). Farmers carry out intensive land management to achieve high production with the addition of chemical fertilizers and pesticides which in the long term can damage the soil and reduce soil fertility. To maintain high production, it is necessary to evaluate soil fertility in dry land agriculture in Baturiti District. The purpose of this study was to determine the status of fertility, as well as to determine the limiting factors of soil fertility, and provide direction for soil management in Dry Land Agriculture, Baturiti District. The research method used is a survey and soil test method with parameters of fertility status including Cation Exchange Capacity (CEC), Base Saturation (BS), organic-C, total-P, and total-K with reference to the Technical Instructions for Evaluation of Soil Fertility Research Center Bogor land. The results showed that the soil fertility status at the study site was classified into three soil fertility statuses, namely, low with an area of 971.88 ha in HLU I (Parean Tengah Village), classified as medium with 1,023.08 ha found in HLU V (Luwus Village), HLU IX (Antapan Village), HLU VII (Candikuning Village), and a height with an area of 3,082.98 ha are located in HLU IV (Antapan Village), HLU II (Antapan Village), HLU III (Baturiti Village), HLU VIII (Bangli Village) ), HLU VI (Angseri Village). Parameters that are limiting factors for soil fertility status are CEC and C-organic so it is necessary to add organic matter such as organic fertilizer, manure, compost, return of plant remains and by applying intercropping cultivation and crop rotation on dry land agriculture. in Baturiti District.